THE EFFECTS OF L-NAME AND AGMATINE IN THE NUCLEUS ACCUMBENS CORE REGION ON MORPHINE WITHDRAWAL SYNDROME - Demırkapu, Mahluga Jafarova; Yananlı, Hasan Raci; Mammadov, Elmar; Dervishi, Ina; Kırbaş, Ali; Yaşar, Şafak Recep; Sali, Tzemal (My University, 2020)
Aim: The mesocorticolimbic dopaminergic system, especially the nucleus accumbens, is an important region in opioid dependence and withdrawal. Studies have shown that nitric oxide synthase inhibitors modulate the development of tolerance to opioids, opioid dependence, and withdrawal. In this study, we aimed to investigate the effects of local injections of L-NAME and agmatine into the nucleus accumbens core (NAcc), one of the nucleus accumbens subregions on withdrawal signs and locomotor activity behavior during naloxone-induced withdrawal in morphine-dependent rats. Materials and Methods: Twenty-four adult Sprague-Dawley rats were used in the study. Morphine dependence was developed in all animals after guide cannula implantation into the NAcc region. On the last day of experiment, following bilateral L-NAME, agmatine or artificial cerebrospinal fluid (aCSF, control group) microinjections morphine withdrawal was induced by naloxone. Results: Local administration of agmatine and L-NAME into the NAcc significantly suppressed the jumping number during naloxone induced withdrawal. Local agmatine treatment significantly suppressed the score of teeth chattering, although the L-NAME did not change. No significant difference was observed in withdrawal symptoms such as wet dog shakes and defecation after local agmatine and L-NAME treatment. Agmatine increased stereotypic movements, but did not change locomotor activity behaviors such as ambulatory activity and total covered distance. Local administration of L-NAME into the NAcc did not increase stereotypic and ambulatory movements, and total covered distance during naloxone-induced withdrawal. Conclusion: These results suggest that inhibition of nitric oxide synthesis in NAcc plays a role in morphine withdrawal symptoms, but it is not responsible alone.
Keywords: Genel ve Dahili Tıp; Nörolojik Bilimler; Biyokimya ve Moleküler Biyoloji; Psikiyatri